Penerapan sistem agrosilvopastura untuk optimalisasi lahan Kelompok Petani-Peternak “Setetes Madu” di Kabupaten Kupang - Yofris Puay; Melkianus Pobas; Yudhistira A. N. R Ora; Luisa M. Manek; Yakub Benu (P3HKI - Universitas Muhammadiyah Parepare, 2025)
The “Setetes Madu” group is a group of farmers/livestock breeders located in Camplong II Village, Fatuleu District, Kupang Regency, which is engaged in the field of cattle fattening/paron. The fattening efforts carried out by this group of farmers/livestock breeders have shown significant improvement. However, there is one main problem faced by the target farmer/livestock breeder group, namely the lack of understanding of the intensive, continuous and integrated agricultural land management system between agriculture, forestry and livestock so that it has sustainable results throughout the year. The purpose of the activity is to implement a land management system by combining agricultural components or activities with forestry and livestock components on a land so that it can overcome the problem of land and animal feed availability, increase land productivity, especially on marginal land. The methods used are in the form of counseling and direct practice in the field. Counseling related to the understanding and benefits of applying the Agrosilvopasture method to a land, the economic value and soil conservation value obtained from the application of the agrosilvopasture method. Direct field practice in the form of making agrosilvopasture demonstration plots and making organic fertilizers. The results of the activity are in the form of increasing the knowledge of group members regarding agro-silvopasture, understanding and being able to make bokashi organic fertilizer by utilizing agricultural and livestock waste, increasing the economic value and income of the community from the sale of agricultural crops planted and increasing land productivity.